A phase I clinical trial to evaluate the safety of thymoquinone-rich black cumin oil (BlaQmax®) on healthy subjects: Randomized, double-blinded, placebo-controlled prospective study. (2022) - Thomas, Jestin V.; Mohan, M.E.; Prabhakaran, Prathibha; Das S, Syam; Maliakel, Balu; I.M., Krishnakumar
Abstract: Black cumin or black seed ( Nigella sativa L. ) is a popular medicinal herb and culinary spice belonging to Ranunculacea family. Thymoquinone (TQ) is the major active phytoconstituent in black cumin and is abundant in the volatile oil fraction. Though black cumin oil containing low TQ content (less than 1%) has been clinically investigated, clinical efficacy and safety data of TQ-rich oil is limited. A recent study with black cumin oil formulation containing 5% TQ (BCO-5) exhibited significant clinical efficacy to alleviate sleep disorders and stress. So, the present phase 1 randomized, double-blinded, placebo-controlled trial evaluated the safety of BCO-5 at a dose of 200 mg/adult/day for 90 days on healthy subjects (n = 70). Both the biochemical and hematological parameters were analysed along with the adverse events or side effects to establish the clinical safety of BCO-5. The study reported neither serious adverse side effects nor any significant alterations in the hematological parameters. The absence of significant changes in the biochemical parameters related to liver function (ALT, AST, ALP), renal function (serum creatinine and urea) were also observed. However, analysis of lipid profile showed a significant ( P < 0.05) reduction in total cholesterol, LDL, VLDL and triglycerides, but within the normal range. In conclusion, BCO-5 is safe at 200 mg/adult/day for human consumption and may be clinically evaluated for various health beneficial pharmacological activities where black cumin oil has been shown to have positive effects.